The Relationship Between Fluency in Speaking Arabic and Self-Confidence to Presentation Skills - Prayetno, Eko; Abidin, Munirul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
The high number of Arabic Language Education who have not been able to speak and present using Arabic on campus from among students is a problem for the Arabic language education department. This happens because students prefer to speak Indonesian instantly on campus on an ongoing basis rather than trying to practice speaking Arabic autodidactically. One of the reasons is because of their lack of confidence about Arabic qowaid and learning by themselves. This study aims to determine the relationship between the effect of students' fluency in speaking Arabic and self-confidence on presentation skills in class. The research was conducted with a quantitative approach to Arabic Language Educationof IAIN Kendari. Data was collected in a focused manner using google form through social media, namely WhatsApp. The data was analysed using SPSS 21 to find the correlation between the relationship between fluency in speaking Arabic and self-confidence on the ability of Arabic presentation in the class of Arabic Language Education iain kendari students. The results showed that the ability of fluency in Arabic in class had a positive and significant impact on the influence of fluency in speaking Arabic and self-confidence on presentation ability.